The effect of nitric oxide on synaptic vesicle proton gradient and mitochondrial potential of brain nerve terminals - A. S. Tarasenko (The Ukrainian Biochemical Journal, 2015)
The effect of nitric oxide on synaptic vesicle proton gradient and membrane potential of rat brain nerve terminals was studied. It has been shown that nitric oxide in the form of S-nitrosothiols at nanomolar concentrations had no effect on the studied parameters, but caused a rapid dissipation of synaptic vesicle proton gradient and depolarization of mitochondrial membrane in the presence of a SH-reducing compound such as dithiothreitol. Both processes were reversible and the rate of H+-gradient restoration depended on the redox potential of nerve terminals, namely the molar ratio of reductant/oxidant. This facts, as well as insensitivity of the studied processes to the inhibitor of NO-sensitive guanylate cyclase such as ODQ, allow suggesting that post-translational modification of thiol residues of the mitochondrial and synaptic vesicle proteins underlies the effect of nitric oxide on the key functional parameters of presynaptic nerve terminals.